Analisis Yuridis Tanggung Jawab Negara (State Responsibility) Terhadap Serangan Siber Oleh Aktor Non-Negara Dalam Perspektif Hukum Internasional - Syahputra, Rifky Justicyo; Triadi, Irwan (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
The digital era has increased global dependence on cyber infrastructure, yet it has also created vulnerabilities to transnational cyberattacks. This phenomenon becomes legally complex when attacks are carried out by non-state actors, raising fundamental questions about the accountability of the state from which such attacks originate. This research aims to analyze the application of the principle of state responsibility in international law, particularly concerning how the actions of non-state actors can be attributed to a state. Furthermore, this study identifies the fundamental juridical challenges in the process of evidence-gathering and law enforcement against states suspected of involvement or negligence. Using a normative legal research method with a statute approach and a case study approach, this article examines primary and secondary legal sources such as the Articles on Responsibility of States for Internationally Wrongful Acts (ARSIWA), the UN Charter, and relevant doctrines including the Tallinn Manual 2.0. The findings indicate that the attribution standard based on 'effective control' is difficult to meet in the context of anonymous and decentralized cyberattacks. Consequently, the focus of responsibility shifts to the breach of the due diligence obligation, where a state can be held accountable if proven negligent in preventing or responding to malicious cyber activities from its territory. Nevertheless, significant challenges remain in terms of technical evidence and the limitations of effective, non-escalatory international enforcement mechanisms